DESCRIPTION OF FAMILY PLANNING IMPLANT ACCEPTORS OF HYPERMENORRHEA AND ANEMIA IN BPM RUSMINI SUMBERGEMPOL VILLAGE, SUMBERGEMPOL DISTRICT, TULUNGAGUNG REGENCY - Widya Lusi Arisona; Siti Maryam; Dian Safitri (Universitas STRADA Indonesia, 2023)
The population of all implant family planning acceptors. After being calculated, the sample size is 14 respondentsThe age characteristics of the respondents are mostly > 30 years, namely 4 respondents (57%), for the work of almost all respondents, namely as housewives, namely 12 respondents (86%), in terms of education, almost all of them are elementary-high school, namely 12 respondents (86% ), while based on the number of children born, most of them were aged 2 (86%), then for the length of time using family planning, most of them ranged from 5 years, namely 9 respondents (64%), and for the age of the youngest children, half were aged 2 years and > 2 years as many as 7 respondents and the same between the two (50%)